PENGARUH OLAHRAGA JALAN KAKI TERHADAP SKOR SKALA DEPRESI PADA LANSIA DI RW 01 KECAMATAN CINERE KOTA DEPOK - Desak Nyoman Sithi (Fakultas Ilmu kesehatan UPN Veteran Jakarta, 2019)
Depression was disease depression mood, disease depression more than grief or sorrow. Elderly have problems in his life, not just about the physical condition there were however several other problems, one of which was depression.One ways to consume and reduce boredom was by way of sports walk because walk would be very useful to raise its elderly VO2 maximum. The study was done to know the influence of sports walking to a decrease in the depression in elderly in rw 01 in cinere depok. A design study used was quasy experiment pretest and posttest without control group with the subject of study were 20 respondents to technique purvosive sampling. The study was obtained by using a questionnaire 30 questions geriatric depression scale.The analysis of the statistics using uji-t dependent. The results showed (p value = 0,001, CI 95%) was the sport walking on the scale of depression elderly in rw 01 in cinere depok.